Genetic diversity and mutant detection of Dendrobium bicaudatum using SRAP markers - IDA AYU PUTRI DARMAWATI; YUYUN FITRIANI; GEDE WIJANA; WAFA’ NUR HANIFAH; RINDANG DWIYANI; NI LUH MADE PRADNYAWATHI; FITRIA DWI DARMAYATI (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Darmawati IAP, Fitriani Y, Wijana G, Hanifah WN, Dwiyani R, Pradnyawathi NLM, Darmayati FD. 2026. Genetic diversity and mutant detection of Dendrobium bicaudatum using SRAP markers. Biodiversitas 27 (2): d270223. https://doi.org/10.13057/biodiv/d270223. Natural occurring mutations have been an important source of genetic diversity and new phenotypes for ornamental plants. However, the occurrence rate is relatively low for most plants, including Dendrobium bicaudatum. Mutation induction triggers mutations in plants and can be achieved through physical or chemical methods. One widely used chemical is Ethyl Methane Sulphonate (EMS). Molecular techniques can detect genetic changes in mutated orchids early, without the need for the plants to mature. Thus, this study aimed to investigate genetic variation and detect mutants in D. bicaudatum orchids following EMS treatment using Sequence Related Amplified Polymorphism (SRAP). This study used four SRAP primer combinations. The DNA concentration of sample B2.Chimera approaches purity, indicated by an A160/280 ratio of 1.67. The results indicated that the four primers exhibited high orchid polymorphism, ranging from 91% to 100%. A total of 47 loci and 258 DNA bands were generated using four primers, yielding a PIC value of 0.32-0.37. The high level of polymorphism detected by SRAP indicates genetic diversity in mutant plants, which importantly contributes to conservation. The analysis of genetic similarity via dendrograms revealed two primary clusters at a coefficient of 0.23: one comprising albino explants and the other consisting of non-albino explants. This result suggests that albino mutants possess genetic traits that significantly differ from those of non-albinos. Non-albino explants, including chimeras and normals, exhibited high similarity coefficients ranging from 0.63 to 0.96.